Measuring, monitoring and conserving biodiversity in managed tropical forests - Boyle, T.J.B.; Sayer, Jeffrey A. (1995)
Discusses methods for measuring and monitoring different components of biodiversity in tropical forests. Considers the conservation of biodiversity in tropical forests including the use of criteria and indicators, the zonation concept of management, the use of buffer zones, and extractive reserves. Prospects for future conservation and management are discussed.